Tryphon latrator - Ghahari, Hassan (Zenodo, 2016)
Tryphon latrator (Fabricius, 1781) Material examined. Province of Tehran, PAKDAShT, 35°28′N 51°46′E, 1 ♂, 14-15.V.2013 . General distribution. Albania, Austria, Belarus, Belgium, Bulgaria, Czech Republic, Denmark, Estonia, Finland, France, Germany, Hungary, Iceland, Iran, Ireland, Italy, Kazakhstan, Kyrgyzstan, Latvia, Lithuania, Luxembourg, Moldova, Mongolia, Netherlands, Norway, Poland, Romania, Russia, Spain, Sweden, Switzerland, Tajikistan, Turkey, Turkmenistan, Ukraine, United Kingdom, Uzbekistan. Host records. It has been reported from Boiea murana (Curtis, 1827) (Lepidoptera: Crambidae), Orthosia stabilis (Denis & Schifferm̡ller) (Lepidoptera: Noctuidae), Dolerus nigratus (M̡ller, 1776) (Hymenoptera: Tenthredinidae). Published as part of Ghahari, Hassan, 2016, A study on the fauna of Ichneumonidae (Hymenoptera) in the province of Tehran, Iran., pp. 125-132 in Arquivos Entomolóxicos 16 on pages 130-131, DOI: 10.5281/zenodo.12765681